Transient co-singing of offspring and mothers in non-duetting Javan gibbons (Hylobates moloch) - Yi, Yoonjung; Choi, Ahyun; Lee, Saein; Ham, Soojung; Jang, Haneul; Oktaviani, Rahayu; Mardiastuti, Ani; Choe, Jae C. (Frontiers in Ecology and Evolution, 2022)
While the vocalizations of non-human primates were thought to be innate, recent studies have revealed highly flexible vocalizations in immatures. This behavior suggests that social influences have an important role in developing vocalizations. Yet not much is known about how non-human primate vocalization develop and how the vocalizations of immature animals differ between sexes. Here, we analyzed 95 cases of co-singing between mothers and offspring out of 240 female songs from three groups of wild Javan gibbon (Hylobates moloch) in Gunung Halimun-Salak National Park, Indonesia, between 2009 and 2021. Hylobates moloch is one of only two gibbon species with pairs that do not duet. Instead, they produce sex-specific solo songs. We found that both offspring female and male H. moloch follow their mothers’ female-specific songs, similar to other duetting gibbon species. Immatures started co-singing with their mothers from seven months old, but with an average starting age of about 24 months. As female offspring grew older, they co-sung with mothers more often while male offspring did not. After seven years of age, both sexes stopped co-singing with their mothers and started singing alone, following their own sex-specific vocalizations. We did not find any relation between male offspring co-singing and territorial functions (e.g., co-singing more during intergroup encounters or closer to home range borders). Our results suggest that mothers’ songs may trigger male offspring and females to practice singing, but not specifically for males to defend territories. We highlight that despite the absence of duets, H. moloch develop their vocalizations from early infancy and throughout their maturation while co-singing with mothers. However, the level of co-singing varies depending on the sexes. Our study is the first to elucidate the sex-specific trajectories of vocal development in H. moloch across years, indicating that offspring in non-duetting gibbons co-sing with mothers like in duetting species.